Do cuidar e orientar para educar: a contribuição da Educação para fixação de políticas públicas em saúde, à luz do conceito de dignidade humana. - Machado , Andréia Vieira (2010)
This research addresses the issue of care to educate and guide - the contribution of Education for setting public policy in health, in light of the concept of human dignity. Interest in the subject emerges from my experience as a nurse and technical education teacher and graduate of Nursing, where the experiences of the usual return of patients to the hospital for not taking proper care targeted at the time of his discharge. This reality comes the research problem: how to train health professionals, especially nurses, can also take care and guide, educate patients to a better quality of life and to change their reality? Object of study: Palliative Care Program, established at the Institute of Infectious Diseases Emilio Ribas of São Paulo. Purpose: to observe and study the Palliative Care Program implemented at the Institute of Infectious Diseases Emilio Ribas of São Paulo and extract information for patient care in general, in order to improve the quality of their lives and to study the contribution of Education for setting policies Public Health, under the notion of human dignity. It has been hypothesized: if the professionals had a nursing training beyond the care and guidance, that is, to educate - in light of the concept of human dignity, could contribute much to improving the quality of life of prolonged patients and to transform the reality of the patient, if there is voluntary compliance with its understanding of the guidelines. Methodology: qualitative research, of phenomenological nature. Methodological procedures: literature review, desk research and case study. Theoretical framework: we used the area of education, health and anthropology, among them are: SILVA (2003, 2000; OLIVEIRA (2007); OLIVEIRA (2008); PIEPER (2003, 1996, 1998, 1999), among others . The research showed that education is the way to transform reality and improve the quality of life of patients who have chronic diseases. It was evident also curricular components that could contribute to the humanization of health, these are: philosophical anthropology; community education, Pedagogy of the collective-subject, human dignity, educate and educational situation. If nursing professionals want to take a step beyond the care and guidance for educating, necessarily, must understand the meaning of education and be able to propose an educational situation